Co‐cultures of programmable cells of monocytic origin and mesenchymal stem cells do increase osteogenic differentiation. Issue 10 (24th June 2014) - Zachos, Christina; Steubesand, Nadine; Seekamp, Andreas; Fuchs, Sabine; Lippross, Sebastian
ABSTRACT Impaired bone healing can occur with numerous pathologic conditions like trauma, osteoporosis, and infection. Therefore tissue‐engineering strategies that aim to enhance osteogenic differentiation of stem cells in order to accelerate bone healing are a major goal of contemporary regenerative research. In this study we cultivated mesenchymal stem cells (MSC) together with the recently patented programmable cells of monocytic origin (PCMO) to test whether co‐cultures promote an osteogenic differentiation process. PCMO have recently been shown to have pluripotent characteristics and do support the regeneration processes of liver and heart diseases. Quantitative real time PCR expression profiles of osteogenic marker genes such as alkaline phosphatase in co‐cultures of PCMO and MSC showed that MSC differentiated into osteoblast‐like cells more rapidly as compared to mono‐cultures. Alkaline phosphatase expression and enzyme activity levels were highly increased in co‐cultures compared to mono‐cultures of MSC. Tests for mineralized matrix formation also indicated that PCMO have a positive effect on co‐cultured MSC under osteogenic culture conditions. However, analysis of collagen 1A did not show enhanced expression. In summary, PCMO obviously have the ability to promote osteogenic differentiation of MSC in vitro while their own pluripotent potential is not sufficient to develop osteoblast‐like characteristics themselves. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:1264–1270, 2014.